A method for preparing tensile-strength copper-nickel alloy foil and its application

By optimizing the preparation method of copper-nickel alloy foil and utilizing a deposition electrolyte with a specific composition and electrodeposition process, the problems of insufficient surface roughness and tensile strength of copper-nickel alloy foil were solved, resulting in an alloy foil with high strength, high toughness and good adhesion, thus improving the performance of lithium batteries.

CN120625125BActive Publication Date: 2025-10-31GANNAN UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511087411.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-05
Publication Date
2025-10-31
Estimated Expiration
2045-08-05

AI Technical Summary

Technical Problem

Existing copper-nickel alloy foils have excessive surface roughness and low tensile strength, which affects the overall performance of lithium-ion batteries.

Method used

A specific deposition electrolyte, including water, sodium chloride, sodium dodecyl sulfonate, phenylboronic acid-modified isocitric acid, alkanolamine-modified sulfonic acid, copper sulfate, nickel sulfate, and neodymium trichloride, was used to prepare tensile copper-nickel alloy foil by electrodeposition. The current density and temperature were controlled to optimize the electrodeposition effect of metal elements.

Benefits of technology

The surface quality and mechanical properties of the alloy foil were improved, with tensile strength reaching 1288~1351MPa and elongation of 5.8~6.2%. Surface roughness and thickness uniformity were significantly reduced, enhancing the adhesion of the negative electrode active layer and improving the service life and overall performance of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120625125B_ABST
    Figure CN120625125B_ABST
Patent Text Reader

Abstract

This invention relates to a method for preparing and applying a tensile-strength copper-nickel alloy foil, belonging to the field of lithium battery materials technology. The invention synthesizes phenylboronic acid-modified isocitric acid with branched carboxyl and boric acid groups, and amine-modified sulfonic acid with sulfonic acid and amine groups. Utilizing the synergistic effect of these two active materials, the electrodeposition effect of nickel, copper, and neodymium in the electrolyte on the cathode plate can be effectively improved, reducing the electrodeposition grain size of the metal elements, increasing the uniformity of metal element distribution in the alloy foil, reducing the surface roughness of the metal foil, and improving the thickness uniformity and mechanical properties of the alloy foil. The copper-nickel alloy foil prepared by this invention has good strength and toughness, with a tensile strength of 1288~1351 MPa and an elongation of 5.8~6.2%, and also exhibits good appearance and high surface quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for preparing and applying a tensile-strength copper-nickel alloy foil, belonging to the field of lithium battery material technology. Background Technology

[0002] Lithium-ion batteries are rechargeable batteries that primarily function by the movement of lithium ions between the positive and negative electrodes. During charging and discharging, Li... + Intercalation and deintercalation back and forth between the two electrodes: During charging, Li + The lithium is extracted from the positive electrode and inserted into the negative electrode via the electrolyte, placing the negative electrode in a lithium-rich state; the process is reversed during discharge. A lithium-ion battery includes a negative electrode, a positive electrode, a separator, an electrolyte, and a battery casing. The negative electrode includes a negative electrode current collector and a negative electrode active layer loaded on the current collector.

[0003] The negative electrode current collector is the carrier for electron energy transfer. Its heat resistance, mechanical properties, and conductivity directly affect the overall performance of the battery. Currently, copper alloy foil is commonly used as the negative electrode current collector in lithium-ion batteries. However, ordinary copper foil is damaged during the charging and discharging process in the electrolyte. Due to the good corrosion resistance and high oxidation resistance of nickel, copper-nickel alloy foil has been developed to replace copper foil. For example, Chinese patent document CN111321437A discloses a copper-nickel alloy foil and its preparation method. This patent document uses a copper-nickel composite electrolyte system and, based on the electrodeposition characteristics of copper and nickel ions, selects a specific combination of complexing agents and additives to prepare a copper-nickel alloy foil with a thickness of 3–10 μm, a nickel mass fraction of 5.0–15.0%, a maximum surface roughness Rz of 2 μm, a tensile strength of 500–600 MPa, and a moderate elongation. This solves the defect of traditional pure copper double-sided foil being prone to tearing and breakage under thin-thickness conditions. However, the copper-nickel alloy foil prepared in this patent document has a large surface roughness and low tensile strength.

[0004] Therefore, there is an urgent need to develop a method for preparing tensile-resistant copper-nickel alloy foil. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing and applying tensile copper-nickel alloy foil, so as to solve the problems of excessive surface roughness and low tensile strength of current copper-nickel alloy foil.

[0006] This invention provides a method for preparing a tensile-strength copper-nickel alloy foil, comprising the following steps: placing an anode plate and a cathode plate in a deposition electrolyte for electrodeposition to obtain a tensile-strength copper-nickel alloy foil on the cathode plate; the deposition electrolyte is composed of water, sodium chloride, sodium dodecyl sulfonate, phenylboronic acid-modified isocitric acid, alkanolamine-modified sulfonic acid, copper sulfate, nickel sulfate, and neodymium trichloride; the concentration of sodium chloride is 0.03~0.05 g / L, the concentration of sodium dodecyl sulfonate is 0.06~0.09 g / L, the concentration of phenylboronic acid-modified isocitric acid is 20~30 g / L, the concentration of alkanolamine-modified sulfonic acid is 30~40 g / L, the concentration of copper sulfate is 85~110 g / L, the concentration of nickel sulfate is 8~15 g / L, and the concentration of neodymium trichloride is 2~2.5 g / L; the chemical structure of the phenylboronic acid-modified isocitric acid is shown below:

[0007] ;

[0008] The chemical structure of the alcoholamine-modified sulfonic acid is as follows:

[0009] .

[0010] Preferably, the temperature of the deposition electrolyte is 35~45℃.

[0011] Preferably, the current density during electrodeposition is 20~35 A / dm³. 2 .

[0012] Preferably, the average thickness of the tensile copper-nickel alloy foil is 7~7.5μm.

[0013] Preferably, the nickel content in the tensile copper-nickel alloy foil is 9.1-9.9% by mass, and the neodymium content is 1.2-1.6% by mass.

[0014] Preferably, the preparation method of the phenylboronic acid modified isocitric acid is as follows: 4-formyl chloride phenylboronic acid and isocitric acid are mixed and reacted, and after purification, phenylboronic acid modified isocitric acid is obtained; the molar ratio of 4-formyl chloride phenylboronic acid and isocitric acid is 1.05~1.1:1.

[0015] Preferably, the reaction time of the 4-formylchlorophenylboronic acid and isocitric acid is 5-7 hours.

[0016] Preferably, the preparation method of the alcohol amine modified sulfonic acid is as follows: allyl sulfonic acid and diisopropanolamine are mixed and reacted at 55~65℃ for 6~8h, and after purification, alcohol amine modified sulfonic acid is obtained.

[0017] Preferably, the molar ratio of allyl sulfonic acid to diisopropanolamine is 1:1.1~1.3.

[0018] This invention provides a method for preparing tensile copper-nickel alloy foil as described above, which is used as a negative electrode current collector in lithium-ion batteries.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] (1) This invention synthesizes phenylboronic acid modified isocitric acid with branched carboxyl and boric acid groups, and sulfonic acid modified amine with sulfonic acid and amine groups. By utilizing the synergistic effect of the two active substances, the electrodeposition effect of nickel, copper and rare earth element neodymium in the electrolyte on the cathode plate can be effectively improved, the electrodeposition grain size of metal elements can be reduced, the distribution uniformity of each metal element in the alloy foil can be improved, the surface roughness of the metal foil can be reduced, and the thickness uniformity and mechanical properties of the alloy foil can be improved.

[0021] (2) The copper-nickel alloy foil prepared by this invention has good strength and toughness, with a tensile strength of 1288~1351 MPa and an elongation of 5.8~6.2%. It also has a good appearance and high surface quality, with significantly lower surface roughness and thickness uniformity. Finally, the copper-nickel alloy foil prepared by this invention has appropriate roughness and surface chemical properties, and has good adhesion to the negative electrode active layer, which can improve the service life of the lithium battery negative electrode and the overall performance of the battery. Attached Figure Description

[0022] Figure 1 The above is the 1H NMR spectrum of the phenylboronic acid-modified isocitric acid prepared in Example 1 of this invention;

[0023] Figure 2 This is the 1H NMR spectrum of the alcoholamine-modified sulfonic acid prepared in Example 1 of this invention. Detailed Implementation

[0024] The following examples are intended to further illustrate the content of the present invention, rather than to limit the scope of protection of the present invention.

[0025] Example 1

[0026] The method for preparing the tensile copper-nickel alloy foil in this embodiment includes the following steps: adding a deposition electrolyte to an electrolytic cell, then placing the cathode plate and anode plate in the deposition electrolyte, turning on the power supply of the electrolytic cell, heating the deposition electrolyte to 35°C for electrodeposition, and obtaining the tensile copper-nickel alloy foil after deposition is completed on the surface of the cathode plate and then peeling it off; the current density during electrodeposition is 20 A / dm³. 2 The tensile copper-nickel alloy foil prepared in this embodiment has an average thickness of 7.0 μm, and the mass fraction of nickel in the tensile copper-nickel alloy foil is 9.1%, the mass fraction of neodymium is 1.2%, and the balance is copper.

[0027] In this embodiment, the deposition electrolyte is composed of water, sodium chloride, dodecyl phosphate monoester, phenylboronic acid modified isocitric acid, alkanolamine modified sulfonic acid, copper sulfate, nickel sulfate, and neodymium trichloride. The concentration of sodium chloride is 0.03 g / L, the concentration of dodecyl phosphate monoester is 0.06 g / L, the concentration of phenylboronic acid modified isocitric acid is 20 g / L, the concentration of alkanolamine modified sulfonic acid is 30 g / L, the concentration of copper sulfate is 85 g / L, the concentration of nickel sulfate is 8 g / L, and the concentration of neodymium trichloride is 2 g / L.

[0028] The preparation method of phenylboronic acid modified isocitric acid is as follows: 4-Formylchlorophenylboronic acid and anhydrous acetone are added to a reactor and stirred until homogeneous to obtain a 15% (w / w) 4-formylchlorophenylboronic acid solution; isocitric acid and anhydrous acetone are added to a stirred reactor and stirred until homogeneous to obtain a 10% (w / w) isocitric acid solution; the temperature of the isocitric acid solution is adjusted to 0℃, stirring is started, and the 4-formylchlorophenylboronic acid solution is added dropwise to the isocitric acid solution. After the addition is complete, triethylamine is added to the stirred reactor. The mixture was placed in a stirred reactor, and the temperature of the material in the stirred reactor was raised to 25°C. The reaction was continued for 5 hours with stirring. After filtration, the filtrate was rotary evaporated to obtain a concentrated solution. The concentrated solution was then purified by column chromatography to obtain phenylboronic acid-modified isocitric acid. The molar ratio of 4-formylchlorophenylboronic acid, isocitric acid, and triethylamine was 1.05:1:1.2. The eluent for column chromatography purification consisted of petroleum ether, ethyl acetate, and methanol in a volume ratio of 15:2:3. The 1H NMR spectrum of the phenylboronic acid-modified isocitric acid is shown below. Figure 1 As shown, the chemical structure is as follows:

[0029] .

[0030] The preparation method of amine-modified sulfonic acid is as follows: Allyl sulfonic acid and acetonitrile are added to a stirred reactor and stirred until homogeneous to obtain a 15% (w / w) allyl sulfonic acid solution; then diisopropanolamine and imidazole hydrochloride are added to the stirred reactor, heated to 80℃, and stirred under reflux for 6 hours. The resulting liquid is then rotary evaporated to obtain a concentrated solution. The concentrated solution is then purified by column chromatography to obtain amine-modified sulfonic acid. The molar ratio of allyl sulfonic acid to diisopropanolamine is 1:1.1, the mass of imidazole hydrochloride is 5% of the mass of allyl sulfonic acid, and the eluent for column chromatography consists of petroleum ether and methanol in a volume ratio of 13:5. The 1H NMR spectrum of amine-modified sulfonic acid is shown below. Figure 2 As shown, the chemical structure is as follows:

[0031] .

[0032] Example 2

[0033] The method for preparing the tensile copper-nickel alloy foil in this embodiment includes the following steps: adding a deposition electrolyte to an electrolytic cell, then placing the cathode plate and anode plate in the deposition electrolyte, turning on the electrolytic cell power supply, heating the deposition electrolyte to 40°C for electrodeposition, and obtaining the tensile copper-nickel alloy foil after deposition is completed on the cathode plate surface and then peeled off; the current density during electrodeposition is 30 A / dm³. 2 The tensile copper-nickel alloy foil prepared in this embodiment has an average thickness of 7.2 μm, and the mass fraction of nickel in the tensile copper-nickel alloy foil is 9.4%, the mass fraction of neodymium is 1.4%, and the balance is copper.

[0034] In this embodiment, the deposition electrolyte is composed of water, sodium chloride, dodecyl phosphate monoester, phenylboronic acid modified isocitric acid, alkanolamine modified sulfonic acid, copper sulfate, nickel sulfate, and neodymium trichloride. The concentration of sodium chloride is 0.04 g / L, the concentration of dodecyl phosphate monoester is 0.07 g / L, the concentration of phenylboronic acid modified isocitric acid is 25 g / L, the concentration of alkanolamine modified sulfonic acid is 35 g / L, the concentration of copper sulfate is 102 g / L, the concentration of nickel sulfate is 10 g / L, and the concentration of neodymium trichloride is 2.2 g / L.

[0035] The preparation method of phenylboronic acid modified isocitric acid is as follows: 4-Formylchlorophenylboronic acid and anhydrous acetone are added to a reactor and stirred until homogeneous to obtain a 20% (w / w) 4-formylchlorophenylboronic acid solution; isocitric acid and anhydrous acetone are added to a stirred reactor and stirred until homogeneous to obtain a 12% (w / w) isocitric acid solution; the temperature of the isocitric acid solution is adjusted to 2℃, stirring is started, and the 4-formylchlorophenylboronic acid solution is added dropwise to the isocitric acid solution. After the addition is complete, triethylamine is added to the stirring... In a reactor, the material in the stirred reactor was heated to 28°C and stirred for another 6 hours. After filtration, the filtrate was rotary evaporated to obtain a concentrated solution. The concentrated solution was then purified by column chromatography to obtain phenylboronic acid-modified isocitric acid. The molar ratio of 4-formylchlorophenylboronic acid, isocitric acid, and triethylamine was 1.08:1:1.3. The eluent for column chromatography purification consisted of petroleum ether, ethyl acetate, and methanol in a volume ratio of 15:2:3. The chemical structure of phenylboronic acid-modified isocitric acid is shown below:

[0036] .

[0037] The preparation method of amine-modified sulfonic acid is as follows: Allyl sulfonic acid and acetonitrile are added to a stirred reactor and stirred until homogeneous to obtain a 20% (w / w) allyl sulfonic acid solution; then diisopropanolamine and imidazole hydrochloride are added to the stirred reactor, heated to 85°C, and stirred under reflux for 7 hours. The resulting liquid is then rotary evaporated to obtain a concentrated solution. The concentrated solution is then purified by column chromatography to obtain amine-modified sulfonic acid. The molar ratio of allyl sulfonic acid to diisopropanolamine is 1:1.2, the mass of imidazole hydrochloride is 6% of the mass of allyl sulfonic acid, and the eluent for column chromatography consists of petroleum ether and methanol in a volume ratio of 13:5. The chemical structure of amine-modified sulfonic acid is as follows:

[0038] .

[0039] Example 3

[0040] The method for preparing the tensile copper-nickel alloy foil in this embodiment includes the following steps: adding a deposition electrolyte to an electrolytic cell, then placing the cathode plate and anode plate in the deposition electrolyte, turning on the power supply of the electrolytic cell, heating the deposition electrolyte to 45°C for electrodeposition, and obtaining the tensile copper-nickel alloy foil after deposition is completed on the cathode plate surface and then peeled off; the current density during electrodeposition is 35 A / dm³. 2 The tensile copper-nickel alloy foil prepared in this embodiment has an average thickness of 7.5 μm, and the mass fraction of nickel in the tensile copper-nickel alloy foil is 9.9%, the mass fraction of neodymium is 1.6%, and the balance is copper.

[0041] In this embodiment, the deposition electrolyte is composed of water, sodium chloride, dodecyl phosphate monoester, phenylboronic acid modified isocitric acid, alkanolamine modified sulfonic acid, copper sulfate, nickel sulfate, and neodymium trichloride. The concentration of sodium chloride is 0.05 g / L, the concentration of dodecyl phosphate monoester is 0.09 g / L, the concentration of phenylboronic acid modified isocitric acid is 30 g / L, the concentration of alkanolamine modified sulfonic acid is 40 g / L, the concentration of copper sulfate is 110 g / L, the concentration of nickel sulfate is 15 g / L, and the concentration of neodymium trichloride is 2.5 g / L.

[0042] The preparation method of phenylboronic acid modified isocitric acid is as follows: 4-Formylchlorophenylboronic acid and anhydrous acetone are added to a reactor and stirred until homogeneous to obtain a 30% (w / w) 4-formylchlorophenylboronic acid solution; isocitric acid and anhydrous acetone are added to a stirred reactor and stirred until homogeneous to obtain a 15% (w / w) isocitric acid solution; the temperature of the isocitric acid solution is adjusted to 5℃, stirring is started, and the 4-formylchlorophenylboronic acid solution is added dropwise to the isocitric acid solution. After the addition is complete, triethylamine is added to the stirring... In a reactor, the material in the stirred reactor was heated to 30°C and stirred for another 7 hours. After filtration, the filtrate was rotary evaporated to obtain a concentrated solution. The concentrated solution was then purified by column chromatography to obtain phenylboronic acid-modified isocitric acid. The molar ratio of 4-formylchlorophenylboronic acid, isocitric acid, and triethylamine was 1.1:1:1.5. The eluent for column chromatography purification consisted of petroleum ether, ethyl acetate, and methanol in a volume ratio of 15:2:3. The chemical structure of phenylboronic acid-modified isocitric acid is shown below:

[0043] .

[0044] The preparation method of amine-modified sulfonic acid is as follows: Allyl sulfonic acid and acetonitrile are added to a stirred reactor and stirred until homogeneous to obtain a 25% (w / w) allyl sulfonic acid solution; then diisopropanolamine and imidazole hydrochloride are added to the stirred reactor, heated to 90°C, and stirred under reflux for 8 hours. The resulting liquid is then rotary evaporated to obtain a concentrated solution. The concentrated solution is then purified by column chromatography to obtain amine-modified sulfonic acid. The molar ratio of allyl sulfonic acid to diisopropanolamine is 1:1.3, the mass of imidazole hydrochloride is 8% of the mass of allyl sulfonic acid, and the eluent for column chromatography consists of petroleum ether and methanol in a volume ratio of 13:5. The chemical structure of amine-modified sulfonic acid is as follows:

[0045] .

[0046] Comparative Example 1

[0047] The only difference between the preparation method of the tensile copper-nickel alloy foil in this comparative example and the preparation method of the tensile copper-nickel alloy foil in Example 1 is that the concentration of phenylboronic acid modified isocitric acid in the deposition electrolyte used in the preparation method of the tensile copper-nickel alloy foil in this comparative example is 0 g / L, and the concentration of alcohol amine modified sulfonic acid is 50 g / L.

[0048] Comparative Example 2

[0049] The only difference between the preparation method of the tensile copper-nickel alloy foil in this comparative example and the preparation method of the tensile copper-nickel alloy foil in Example 1 is that the concentration of phenylboronic acid modified isocitric acid in the deposition electrolyte used in the preparation method of the tensile copper-nickel alloy foil in this comparative example is 50 g / L, and the concentration of alcohol amine modified sulfonic acid is 0 g / L.

[0050] Comparative Example 3

[0051] The difference between the preparation method of the tensile copper-nickel alloy foil in this comparative example and the preparation method of the tensile copper-nickel alloy foil in Example 1 is that the phenylboronic acid modified isocitric acid in the deposition electrolyte used in the preparation method of the tensile copper-nickel alloy foil in this comparative example is replaced with isocitric acid and phenylboronic acid in a molar ratio of 1:1.

[0052] Comparative Example 4

[0053] The difference between the preparation method of the tensile copper-nickel alloy foil in this comparative example and the preparation method of the tensile copper-nickel alloy foil in Example 1 is that the deposition electrolyte used in the preparation method of the tensile copper-nickel alloy foil in this comparative example replaces the alcoholamine-modified sulfonic acid with allyl sulfonic acid and diisopropanolamine in a molar ratio of 1:1.

[0054] Comparative Example 5

[0055] The difference between the preparation method of the tensile copper-nickel alloy foil in this comparative example and the preparation method of the tensile copper-nickel alloy foil in Example 1 is that neodymium trichloride is replaced with cerium trichloride in the deposition electrolyte used in the preparation method of the tensile copper-nickel alloy foil in this comparative example.

[0056] Comparative Example 6

[0057] The only difference between the preparation method of the tensile copper-nickel alloy foil in this comparative example and the preparation method of the tensile copper-nickel alloy foil in Example 1 is that the dodecyl phosphate monoester is replaced with sodium dodecyl sulfonate in the deposition electrolyte used in the preparation method of the tensile copper-nickel alloy foil in this comparative example.

[0058] Comparative Example 7

[0059] The only difference between the preparation method of the tensile copper-nickel alloy foil in this comparative example and the preparation method of the tensile copper-nickel alloy foil in Example 1 is that the dodecyl phosphate monoester is replaced with sodium monododecyl phosphate in the deposition electrolyte used in the preparation method of the tensile copper-nickel alloy foil in this comparative example.

[0060] Comparative Example 8

[0061] The difference between the preparation method of the tensile copper-nickel alloy foil in this comparative example and the preparation method of the tensile copper-nickel alloy foil in Example 1 is only that the phenylboronic acid-modified isocitric acid used in the deposition electrolyte of this comparative example is replaced with phenylboronic acid-modified citric acid. The preparation method of phenylboronic acid-modified citric acid is as follows: 4-formylchlorophenylboronic acid and anhydrous acetone are added to a reactor and stirred evenly to obtain a 15% (w / w) 4-formylchlorophenylboronic acid solution; citric acid and anhydrous acetone are added to a stirred reactor and stirred evenly to obtain a 10% (w / w) citric acid solution; the temperature of the citric acid solution is adjusted to... At 0℃, stirring was started, and 4-formylchlorophenylboronic acid solution was added dropwise to citric acid solution. After the addition was complete, triethylamine was added to the stirred reactor. The temperature of the material in the stirred reactor was then raised to 25℃, and the reaction was continued for 5 hours. The mixture was filtered, and the filtrate was rotary evaporated to obtain a concentrated solution. The concentrated solution was then purified by column chromatography to obtain phenylboronic acid-modified citric acid. The molar ratio of 4-formylchlorophenylboronic acid, citric acid, and triethylamine was 1.05:1:1.2. The eluent for column chromatography purification consisted of petroleum ether, ethyl acetate, and methanol in a volume ratio of 15:2:3. The chemical structure of phenylboronic acid-modified citric acid is shown below:

[0062] .

[0063] Comparative Example 9

[0064] The difference between the preparation method of the tensile copper-nickel alloy foil in this comparative example and the preparation method of the tensile copper-nickel alloy foil in Example 1 lies only in the chemical structure of the amine-modified sulfonic acid in the deposition electrolyte used in the preparation method of the tensile copper-nickel alloy foil in this comparative example:

[0065] .

[0066] Experimental Example

[0067] To examine the comprehensive performance of the tensile copper-nickel alloy foils prepared in each embodiment and comparative example, the surface roughness, thickness uniformity, tensile strength, and elongation of the tensile copper-nickel alloy foils prepared in each embodiment and comparative example were tested. The test results are shown in Table 1. The thickness uniformity test method is as follows: thickness measurements were performed at 15 test points on each tensile copper-nickel alloy foil to be tested (the 15 test points on different tensile copper-nickel alloy foils were at the same locations). Then, the average thickness was calculated based on the test results. Finally, the ratio of the difference between the maximum and minimum thickness values ​​to the average thickness was calculated to obtain the thickness uniformity. For the surface roughness, tensile strength, and elongation tests, three parallel samples were used, and the average of the test results of the three parallel samples was taken as the final test result. When testing surface roughness, tests are conducted at 5 locations on each tensile copper-nickel alloy foil to be tested (the locations of the 5 test points are the same on different tensile copper-nickel alloy foils to be tested). The average roughness of the 5 test points on each tensile copper-nickel alloy foil to be tested is taken as the surface roughness test result of that tensile copper-nickel alloy foil to be tested.

[0068] Table 1. Surface roughness, thickness uniformity, tensile strength, and elongation of tensile copper-nickel alloy foils.

[0069] Tensile copper-nickel alloy foil Surface roughness (μm) Thickness uniformity Tensile strength (MPa) Elongation (%) Example 1 0.22 0.021 1351 5.8 Example 2 0.15 0.044 1288 6.2 Example 3 0.18 0.032 1349 5.9 Comparative Example 1 1.83 0.125 513 3.7 Comparative Example 2 1.79 0.131 508 3.5 Comparative Example 3 1.75 0.128 424 4.1 Comparative Example 4 1.67 0.136 531 3.8 Comparative Example 5 1.76 0.140 487 4.3 Comparative Example 6 1.82 0.134 593 3.8 Comparative Example 7 1.77 0.122 636 3.6 Comparative Example 8 1.69 0.137 584 4.0 Comparative Example 9 1.58 0.121 651 3.5

[0070] As shown in Table 1, the copper-nickel alloy foil prepared by this invention exhibits high tensile strength (1288~1351 MPa) and good elongation (5.8~6.2%), indicating that the copper-nickel alloy foil prepared by this invention possesses both good strength and toughness. Furthermore, the copper-nickel alloy foil prepared by this invention has low surface roughness and low thickness uniformity, indicating that the copper-nickel alloy foil prepared by this invention has good appearance and good surface quality.

[0071] As can be seen from Example 1 and Comparative Examples 1-2, compared with using phenylboronic acid to modify isocitric acid or alkanolamine to modify sulfonic acid alone, when phenylboronic acid is modified isocitric acid and alkanolamine are modified sulfonic acid simultaneously, the branched carboxyl groups, boric acid groups, alkanolamine groups and sulfonic acid groups can work together to improve the electrodeposition uniformity of metallic nickel, metallic copper and rare earth element neodymium, thereby improving the distribution uniformity of nickel, copper and rare earth element neodymium in the metal foil and the refinement of metal grains, and thus improving the surface quality and mechanical properties of the metal foil.

[0072] As shown in Example 1 and Comparative Examples 3-4, when phenylboronic acid-modified isocitric acid was replaced with isocitric acid and phenylboronic acid in a molar ratio of 1:1, although the electrolyte also contained branched carboxyl groups and boric acid groups, the surface quality and mechanical properties of the prepared alloy foil were significantly reduced. This indicates that branched carboxyl groups and boric acid groups can only exert a better synergistic effect and improve the electrodeposition effect of nickel, copper, and the rare earth element neodymium when they are combined through chemical bonding. Similarly, when alkanolamine-modified sulfonic acid was replaced with allyl sulfonic acid and diisopropanolamine in a molar ratio of 1:1, although the electrolyte also contained sulfonic acid groups and alkanolamine groups, the surface quality and mechanical properties of the prepared alloy foil were significantly deteriorated. This indicates that alkanolamine-modified sulfonic acid can better improve the electrodeposition effect of nickel, copper, and the rare earth element neodymium compared to a mixture of allyl sulfonic acid and diisopropanolamine.

[0073] As can be seen from Example 1 and Comparative Example 5, when neodymium trichloride is replaced with cerium trichloride, although both neodymium and cerium are rare earth metal elements, the surface quality and mechanical properties of the prepared alloy foil are significantly different. This may be because in the electrolyte system of the present invention, neodymium is better than cerium at reducing the electrodeposition grain size of metal elements, thereby improving the uniformity of the distribution of each metal element in the alloy foil, thus improving the electrodeposition effect, reducing roughness, and improving thickness uniformity and mechanical properties.

[0074] As can be seen from Examples 1 and Comparative Examples 6-7, after replacing mono-dodecyl phosphate with sodium dodecyl sulfonate or sodium mono-dodecyl phosphate, although sodium dodecyl sulfonate, sodium mono-dodecyl phosphate, and mono-dodecyl phosphate are all anionic surfactants that have a dispersing and stabilizing effect on copper, nickel, and neodymium ions, in the deposition electrolyte system of the present invention, the use of mono-dodecyl phosphate can improve the deposition effect of metal elements more than the use of sodium dodecyl sulfonate or sodium mono-dodecyl phosphate. This may be because mono-dodecyl phosphate has better compatibility with the components in the electrolyte and contains phosphate groups, which can work together with phenylboronic acid modified isocitric acid and alkanolamine modified sulfonic acid in the electrolyte to play a dispersing and complexing role, thereby improving the deposition effect of metal elements and thus improving the surface quality and mechanical properties of the metal foil.

[0075] As can be seen from Example 1 and Comparative Examples 8-9, when the phenylboronic acid-modified isocitric acid in the deposition electrolyte is replaced with phenylboronic acid-modified citric acid or 3-(bis(2-hydroxyethyl)amino)propane-1-sulfonic acid is used as an alcoholamine-modified sulfonic acid, the surface quality and mechanical properties of the metal foil deteriorate. This indicates that the branched chains in the acidic compound help to improve the electrodeposition effect of nickel, copper and rare earth element neodymium.

[0076] Example of effect

[0077] To further evaluate the application effect of the tensile copper-nickel alloy foils prepared in each embodiment and comparative example as negative electrode current collectors for lithium-ion batteries, negative electrode slurry was coated on the surface of the tensile copper-nickel alloy foil. After drying, a negative electrode active layer was formed. Then, the adhesion of the Cr-Ce alloy coating on the pretreated metal substrate surface was tested using a WS-2005 coating adhesion and scratch tester. The loading speed during the test was 50 N / min, and the scratching speed was 3 mm / min. Three parallel samples were tested, and the average value of the test results of the three parallel samples was taken as the final test result. The test results are shown in Table 2. The preparation method of the negative electrode slurry is as follows: graphite, carboxymethyl cellulose, carbon black conductive agent, and styrene-butadiene rubber in a mass ratio of 95:2:3:4 were stirred evenly to obtain the negative electrode slurry.

[0078] Table 2 Adhesion of the negative electrode active layer on tensile copper-nickel alloy foil

[0079] Tensile copper-nickel alloy foil Adhesion (N) Tensile copper-nickel alloy foil Adhesion (N) Example 1 52 Comparative Example 4 7 Example 2 45 Comparative Example 5 6 Example 3 48 Comparative Example 6 9 Comparative Example 1 8 Comparative Example 7 8 Comparative Example 2 7 Comparative Example 8 7 Comparative Example 3 6 Comparative Example 9 9

[0080] As shown in Table 2, the tensile-strength copper-nickel alloy foil prepared by this invention exhibits good adhesion to the negative electrode active layer. This is likely due to the appropriate surface roughness and surface chemical properties of the tensile-strength copper-nickel alloy foil. In summary, the tensile-strength copper-nickel alloy foil prepared by this invention is expected to improve the service life of lithium battery negative electrode sheets and the overall performance of the battery.

Claims

1. A method for preparing a tensile-strength copper-nickel alloy foil, characterized in that, Includes the following steps: An anode and cathode plate are placed in a deposition electrolyte for electrodeposition, resulting in a tensile-strength copper-nickel alloy foil on the cathode plate. The deposition electrolyte comprises water, sodium chloride, sodium dodecyl sulfonate, phenylboronic acid-modified isocitric acid, alkanolamine-modified sulfonic acid, copper sulfate, nickel sulfate, and neodymium trichloride. The concentrations are as follows: sodium chloride 0.03–0.05 g / L, sodium dodecyl sulfonate 0.06–0.09 g / L, phenylboronic acid-modified isocitric acid 20–30 g / L, alkanolamine-modified sulfonic acid 30–40 g / L, copper sulfate 85–110 g / L, nickel sulfate 8–15 g / L, and neodymium trichloride 2–2.5 g / L. The chemical structure of the phenylboronic acid-modified isocitric acid is shown below. ; The chemical structure of the alcoholamine-modified sulfonic acid is as follows: 。 2. The method for preparing the tensile copper-nickel alloy foil as described in claim 1, characterized in that, The temperature of the deposition electrolyte is 35~45℃.

3. The method for preparing tensile copper-nickel alloy foil as described in claim 1, characterized in that, The current density during electrodeposition is 20~35 A / dm. 2 .

4. The method for preparing the tensile copper-nickel alloy foil as described in claim 1, characterized in that, The average thickness of the tensile copper-nickel alloy foil is 7~7.5μm.

5. The method for preparing tensile copper-nickel alloy foil as described in claim 1, characterized in that, The tensile copper-nickel alloy foil contains 9.1-9.9% nickel and 1.2-1.6% neodymium by mass.

6. The method for preparing the tensile copper-nickel alloy foil according to any one of claims 1-5, characterized in that, The preparation method of the phenylboronic acid modified isocitric acid is as follows: 4-formyl chloride phenylboronic acid and isocitric acid are mixed and reacted, and after purification, phenylboronic acid modified isocitric acid is obtained; the molar ratio of 4-formyl chloride phenylboronic acid and isocitric acid is 1.05~1.1:

1.

7. The method for preparing the tensile copper-nickel alloy foil as described in claim 6, characterized in that, The reaction time for the mixture of 4-formylchlorophenylboronic acid and isocitric acid is 5-7 hours.

8. The method for preparing the tensile copper-nickel alloy foil according to any one of claims 1-5, characterized in that, The preparation method of the alcohol amine modified sulfonic acid is as follows: allyl sulfonic acid and diisopropanolamine are mixed and reacted at 80~90℃ for 6~8h, and after purification, alcohol amine modified sulfonic acid is obtained.

9. The method for preparing the tensile copper-nickel alloy foil as described in claim 8, characterized in that, The molar ratio of allyl sulfonic acid to diisopropanolamine is 1:1.1~1.

3.

10. The application of a tensile copper-nickel alloy foil prepared by the method described in any one of claims 1-9 as a negative electrode current collector for a lithium-ion battery.

Citation Information

Patent Citations

  • Copper-nickel alloy foil and electro-deposition preparation method thereof

    CN111321437A

  • Manufacturing process of smooth roughened electrolytic copper foil

    CN102277605A

  • KR20190078392A